3 - Le capital de confiance initial des régimes militaires africains: by Niandou Souley Abdoulaye - Niandou Souley Abdoulaye, (Africa Development, 1995)
The author studies African contemporary armies on the basis of ' Initial Cepita! Hope ' This study helps him to uncover the various strategies of confiscation, conservation and manipulation of the state. He underscores the weakness of developmental studies which fail to take account of the non-homogeneous character of the army in Africa and which also is a transmission belt of the conflicts and partitions of ethnic , regional and inter-army nature despite the unifying pretensions.